Using Engaging Activities to Enhance Student Mental Wellness in Introductory Economics Classes - Stefani Milovanska-Farrington; Dirk Mateer (Institute of Labor Economics (IZA), 2025)
Many college students experience symptoms of mental health challenges, with depression and anxiety being among the most common. These problems negatively affect academic performance (Brännlund et al. 2017) and overall health (Yang et al. 2024). In the 2021 Healthy Minds Study, 41% of the participating students tested positive for depression, 34% suffered from anxiety, 12% had an eating disorder, 40% were diagnosed with a lifetime mental disorder, and 13% reported suicidal thoughts in the previous year (Eisenberg et al. 2021). These statistics are both concerning and unfortunate given that there are easy ways to maintain good mental health. In this paper, we propose engaging activities that can be implemented in introductory economics classes to illustrate economic concepts while promoting wellness. Learning activities that promote wellness in economics serve a twofold purpose: knowledge acquisition and better mental health outcomes for students, both of which are public goods.
Keywords: A20; A21; 330; activities; engagement; engaging activities; foundation economics; games; mental health; music; teaching economics; wellness